Marker counter-selection via CRISPR/Cas9 co-targeting for efficient generation of genome edited avian cell lines and germ cells. Issue 6 (18th November 2022) - Challagulla, Arjun; Shi, Shunning; Nair, Kiran; O'Neil, Terri E.; Morris, Kirsten R.; Wise, Terry G.; Cahill, David M.; Tizard, Mark L.; Doran, Timothy J.; Jenkins, Kristie A.
Abstract: Efficient isolation of genetically modified cells that are phenotypically indistinguishable from the unmodified cells remains a major technical barrier for the broader utilization of CRISPR/Cas9. Here, we report a novel enrichment approach to select the genome engineered cells by co-targeting a genomically integrated GFP gene along with the endogenous gene of interest (GOI). Using this co-targeting approach, multiple genomic loci were successfully targeted in chicken (DF1) and quail (CEC-32) fibroblast cell lines by transient transfection of Cas9 and guide RNAs (gRNAs). Clonal isolation of co-targeted DF1 cells showed 75% of cell clones had deletion of GFP and biallelic deletion of the GOI. To assess the utility of this approach to generate genome modified animals, we tested it on chicken primordial germ cells (PGCs) expressing GFP by co-targeting with gRNAs against GFP and endogenous ovomucoid (OVM) gene. PGCs enriched for loss of GFP and confirmed for OVM deletion, derived by co-targeting, were injected into Hamburger and Hamilton stage 14–15 chicken embryos, and their ability to migrate to the genital ridge was confirmed. This simple, efficient enrichment approach could easily be applied to the creation of knock-out or edited cell lines or animals.